STRUCTURE OF BORROWED ADJECTIVES IN RUSSIAN LINGUISTIC LITERATURE - Akhunova Maftuna Bahodir qizi (The Conference Hub, 2025)
This article explores the structure of borrowed adjectives in Russian linguistic literature, emphasizing their origins, adaptation methods, and functional roles. Borrowed adjectives enter the Russian language through cultural, economic, and political interactions, significantly enriching its vocabulary. The paper examines the primary sources of borrowing, including Latin, Greek, French, English, German, and Turkic languages, and discusses morphological adaptation processes such as suffixation, prefixation, and phonetic changes. Additionally, the study highlights the stylistic, terminological, and foreign-language influences of borrowed adjectives in various literary contexts. The impact of borrowed adjectives on the Russian language is analyzed, addressing ongoing debates about their benefits and potential drawbacks. The article concludes that borrowed adjectives contribute to the dynamic development of Russian, expanding its expressive capabilities and reflecting broader trends of linguistic globalization.
Keywords: Borrowed adjectives, Russian language, Linguistic literature, Language borrowing, Morphological adaptation, Latin and Greek influence, French borrowings